2023
DOI: 10.1093/mnras/stad3649
|View full text |Cite
|
Sign up to set email alerts
|

X-ray polarization properties of thermal-radiative disc winds in binary systems

Ryota Tomaru,
Chris Done,
Hirokazu Odaka

Abstract: New X-ray polarization results are challenging our understanding of the accretion flow geometry in black hole binary systems. Even spectra dominated by a standard disc can give unexpected results, such as the high-inclination black hole binary 4U 1630−472, where the observed X-ray polarization is much higher than predicted. This system also shows a strong, highly ionized wind, consistent with thermal-radiative driving from the outer disc, leading to speculation that scattering in the wind is responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Further, for the reflected flux to make a significant contribution to the total spectrum, the solid angle subtended by the wind to the X-ray source needs to be large; in this case, emission lines should be present, which we do not see in the NICER and NuSTAR energy spectra. Recently, Tomaru et al (2024) studied a possible wind contribution to the polarization and concluded that the wind cannot explain the very high PDs observed in this source. Finally, in a subsequent observation of the source, when it exhibited an SPL state and no evidence for a wind was apparent, the PD and its energy dependence were similar to the high-soft state (Rodriguez Cavero et al 2023), again arguing against a wind origin for the polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Further, for the reflected flux to make a significant contribution to the total spectrum, the solid angle subtended by the wind to the X-ray source needs to be large; in this case, emission lines should be present, which we do not see in the NICER and NuSTAR energy spectra. Recently, Tomaru et al (2024) studied a possible wind contribution to the polarization and concluded that the wind cannot explain the very high PDs observed in this source. Finally, in a subsequent observation of the source, when it exhibited an SPL state and no evidence for a wind was apparent, the PD and its energy dependence were similar to the high-soft state (Rodriguez Cavero et al 2023), again arguing against a wind origin for the polarization.…”
Section: Discussionmentioning
confidence: 99%